CFD-Preliminary Design and Stability Analysis of a High-Speed Firefighting Boat for Remote Island Waterways - Wirawan, Moh.Winki; Oloan, Achdri Fauzi Nugraha; Subakti, Albert Gabriel; Batosai, Joan Rike (Naval Architecture Department, Kalimantan Institut of Technology, 2024)
The Seribu Islands, administered by the DKI Jakarta Provincial Government, cover an area of 4,745.62 km², with 8.76 km² of land spread across two sub-districts and six major islands: Kelapa, Harapan, Panggang, Tidung, Pari, and Untung Jawa. While these islands are popular tourist destinations with adequate transport facilities, the remote, water-surrounded nature of the area poses challenges for emergency response, particularly firefighting. To address this, the authors designed a firefighting vessel optimized for quick deployment and effective fire suppression. The design process focused on determining optimal dimensions and minimizing hydrodynamic resistance through hull variation using effect of length on resistance method, followed by exponential regression. The vessel’s main dimensions are LOA 16.5 m, LPP 15.588 m, beam 4.9 m, depth 2.5 m, draft 0.9 m, and a top speed of 36 knots. Four hull configurations with varying chine type and angles (0°, 10°, and 17°) were simulated in Numeca Fine Marine (CFD) and Maxsurf. The third hull variation achieved the lowest resistance, with a resistance value of 67.12 kN. Equipped with a pump capacity of 474 m³/h and a spray range of 25 m, the vessel provides effective firefighting capabilities. Stability analysis, including fire monitor placement variations, indicates the optimal trim and stability with a Max GZ angle of 50° and a roll period of 3.14 seconds. This design demonstrates a feasible solution for firefighting within the Seribu Islands’ unique aquatic environment.